Theoretical perspectives of the HCD integration in software development process - Rogayah Abdul Majid; Nor Laila Md. Noor; Wan Adilah Wan Adnan (Institute of Advanced Engineering and Science, 2020)
HCD is an approach that covers all of the human aspects including aesthetic and ergonomics, which will provide a better approach in strengthening the HCI approaches to strengthen the software development process. Lack of guidelines to guide the software practitioners to adopt the HCD in software development process become the main concern in this study. Among the problems that faced by the organizations that have adopted HCD, including problem of managing the resources such as human, financial and infrastructure. Therefore, this study used a theoretical lens to get a better understanding of HCD integration form management perspective, namely operational, tactical (management) and strategy perspective in software development process. Furthermore, the HCDP model is employed in this study because it covers the HCD activities from the project planning stage to the implementation stage of the software development process and it emphasizes on the larger scope of human factors and require broader skills in software development process. As a result, a conceptual model of HCD integration has been developed which emphasizes on the importance of managing the resources and long term strategic planning for the organization. This is due to long term strategic planning and managing organization resources appropriately will contribute to the success of the organization which will increase organizational performance.